FAKTOR -FAKTOR YANG MEMPENGARUHI KUNJUNGAN IBU HAMIL DI WILAYAH KERJA PUSKESMAS PELAIHARI KABUPATEN TANAH LAUT - virgianti, risa; Dewi Iswandari, Novita; Vidiasari Darsono, Putri; Lestari, Yayuk Puji (Midwifery And Complementary Care, 2024)
Background: Puskesmas as one of the health service facilities has a strategic role in efforts to improve the degree of public health at large. The main role of Puskesmas is to provide quality services to individuals, families, groups and communities to achieve maximum health status. Purpose: Knowing the factors that affect the visit of pregnant women in the working area of the Pelaihari Health Center, Tanah Laut Regency. Methods: Type of quantitative research with a crosssectional approach. Sample of 68 pregnant women. The sampling technique uses accidental sampling. The instrument used univariate and bivariate Chi-square analyzed questionnaires. Result: Univariate results of maternal age 98.5% of the non-risk category, low category education as much as 61.8%, remote home category 52.9%, the most knowledge of the less category is 54.4%, and the husband category supports 75%. The results of the study statistically factor age (p value 0.324) was not related to visits of pregnant women, education (p value 0.007) was related to visits of pregnant women, distance from home (p value 0.799) was not related to visits of pregnant women. Knowledge (p value 0.615) is not related to visits by pregnant women, and husband support (p value 0.385) is not related to visits by pregnant women in the Working Area of Pelaihari Health Center. Conclusion: Factors that are not related to pregnant women's visits are age, home distance, knowledge and husband support. While the related factor is the mother's education. So that health workers can innovate by means of education to adjust maternal education. Keywords: Husband Support, Home Distance, Education, Knowledge, Age.